2015
DOI: 10.1093/jxb/erv148
|View full text |Cite
|
Sign up to set email alerts
|

The dominant negative ARM domain uncovers multiple functions of PUB13 in Arabidopsis immunity, flowering, and senescence

Abstract: HighlightEctopic expression of the PUB13 ARM domain in planta mimics the pub13 mutant with enhanced immune responses, stress-induced leaf senescence, and early flowering.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(72 citation statements)
references
References 51 publications
3
67
2
Order By: Relevance
“…Recently, ubiquitination regulation of leaf senescence has attracted increasing attention (Kim et al ., ). The U‐box E3 ligases, PUB12 and PUB13, as well as the RING E3 ligase, ATL31, have been found to function as repressors during leaf senescence (Aoyama et al ., ; Zhou et al ., ). In this study, we found that, in addition to the gene expression of MdbHLH93 (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…Recently, ubiquitination regulation of leaf senescence has attracted increasing attention (Kim et al ., ). The U‐box E3 ligases, PUB12 and PUB13, as well as the RING E3 ligase, ATL31, have been found to function as repressors during leaf senescence (Aoyama et al ., ; Zhou et al ., ). In this study, we found that, in addition to the gene expression of MdbHLH93 (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…However, rice ATPase XB24 promotes XA21 autophosphorylation via its ATPase activity but inhibits XA21-mediated resistance (21). The Arabidopsis E3 ubiquitin ligases PUB12 and PUB13 are recruited to FLS2 in a BAK1-dependent manner and directly ubiquitinate FLS2 for FLS2 degradation, leading to the attenuation of FLS2 signaling (99, 175). Ubiquitination of membrane receptors also leads to receptor endocytosis and lysosome/vacuole targeting.…”
Section: Pattern Recognition Receptor Complexes Perceiving Patternsmentioning
confidence: 99%
“…Yeast two-hybrid (Y2H) and Co-IP experiments using the BAK1 kinase domain as a bait demonstrated that flg22 treatment stimulates interaction between BAK1 and the plant U box (PUB) E3 ubiquitin ligases PUB12 and PUB13, and that the BAK1-PUB12/13 complex associates with FLS2 within 30 seconds of flg22 treatment [12]. Kinase assays using protoplasts expressing BAK1 or a kinase-inactive mutant indicated that BAK1 phosphorylates the C-terminal Armadillo (ARM) repeat domain of PUB13 in response to flg22 treatment, and chemical inhibition of kinase activity confirmed that BAK1-dependent phosphorylation is required for flg22-induced FLS2-PUB12/PUB13 interaction [12,13]. In vitro ubiquitination assays confirmed that PUB12 and PUB13 polyubiquitinate the cytosolic domain of FLS2, but not BAK1 or BIK1 [12].…”
Section: Ubiquitination and N-glycosylation Contribute To Pti Throughmentioning
confidence: 99%